"Drang nach Westen". Rozwój przemysłowy Dolnych Łużyc a napływ ludności polskiej na przełomie XIX i XX wieku = "Drang nach westen". Thrust toward the west. The industrial development in Lower Lusatia and the surge in Polish immigration at the turn of the 20th century - Belzyt, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the 18th, but even more in the 19th and 20th century, the Industrial Revolution initiated a massive and historically unrivaled rearrangement of cultural landscapes in the highly developed European countries, i.e. in England, France, and Germany, to just name the most relevant ones. This European example was then followed by other countries in North America and - much later - in South America and Asia.
Keywords: Dolne Łużyce; Drang nach Westen; migracje; industrializacja; Lower Lusatia; migrations; industrialisation